Barvanje točk grafov - Batagelj, Vladimir (Informatica (Ljubljana), 1985)
In the paper the survey of most important results on the theoretic and algorithmic aspects of the graph coloring problem is given. A heuristic procedure which combines the Szekeres-Wilf and Brélaz coloring procedure is presented at the end.
Keywords: algorithms; algoritmi; barvanje grafov; coloring procedures; graph coloring; graph theory; lastnosti barvnosti; matematika; mathematics; ocene barvnosti; teorija grafov